Interpretive structural modelling: Hierarchical relationship model of appreciating diversity competency for educational leaders - Noraini Abdul Latiff; Muhammad Faizal A. Ghani (Institute of Advanced Engineering and Science, 2023)
The dynamics of diversity and cultural competency are elements that run parallel with globalization. Appreciating diversity is part of global leadership competency. However, this assumption may not hold in a context in which multiculturalism diversity and competency are not an integral element for leadership competency for public sector educational leaders. Public organization should assimilate and practice appreciating diversity in the organizational leadership competency. Thus, the central aim of this study is to investigate and examine the appreciating diversity competency for educational leaders. The paper analyzed the appreciating competencies by using interpretive structural modelling (ISM) based on experts’ consensus. The cross-impact matrix multiplication applied to classification (MICMAC) analysis ascertained and classified each competency based on their driving and dependent power. The hierarchical model developed through ISM yielded seven appreciating competencies divided into two dimensions for educational leaders. The model proposed could be adopted by stakeholders to upgrade the competency of educational leaders to practice and apply appreciating diversity. The ISM model could be adopted for the training and development of future educational leaders in preparation to administer and lead multicultural and multigenerational organizational communities.